Where is the Love? Considering Compassion's Role in Public Values Scholarship. (3rd May 2020) - Masters, Adam B.
Abstract : In the late 19th and early 20th century, modern states began to take responsibility for the welfare of citizens. Nations did this in different ways, but primarily in response to the social changes – such as urbanization and industrialization – that meant the traditional providers of welfare like churches and philanthropic organizations were overwhelmed. Shifting forward a hundred years to the late 20th and early 21st century, the same states are now retreating from the delivery (at least) of such services. The churches and philanthropies – who never ceased to provide healthcare – now find themselves involved in public-private partnerships to deliver care to the sick, aged, mentally ill, and disabled people. These organizations operate with their own value sets, which poses the question – are private values public values when they frame the delivery of public goods? This article looks at one private-public value – compassion – which has been subsumed in our studies of public values into a variety of meta-values. Using the Australian healthcare system – which is relatively balanced between public and private delivery – this essay unlocks compassion's role as a private value in a public sphere.